2022
DOI: 10.1038/s41398-022-02078-7
|View full text |Cite
|
Sign up to set email alerts
|

TOB is an effector of the hippocampus-mediated acute stress response

Abstract: Stress affects behavior and involves critical dynamic changes at multiple levels ranging from molecular pathways to neural circuits and behavior. Abnormalities at any of these levels lead to decreased stress resilience and pathological behavior. However, temporal modulation of molecular pathways underlying stress response remains poorly understood. Transducer of ErbB2.1, known as TOB, is involved in different physiological functions, including cellular stress and immediate response to stimulation. In this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…In neurons, the nonsense-mediated RNA decay (NMD) pathway serves as a regulatory mechanism to control mRNA, and mutations in the NMD genes have been associated with neurodevelopmental disorders, such as schizophrenia and neurodegenerative disorders, such as amyotrophic lateral sclerosis (Jaffrey and Wilkinson, 2018). TOB1, which codes for an antiproliferative protein that targets Frontiers in Genetics frontiersin.org mRNA deadenylation and decay (Hosoda et al, 2011), has previously been associated with neurodegenerative disorders (Weskamp and Barmada, 2018), such as multiple sclerosis (Gironi et al, 2016) and a TOB1 deletion has been associated with hippocampus-mediated acute stress response in animal models (Youssef et al, 2022). The primary role of the signal transduction pathway is to regulate overall growth and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, the nonsense-mediated RNA decay (NMD) pathway serves as a regulatory mechanism to control mRNA, and mutations in the NMD genes have been associated with neurodevelopmental disorders, such as schizophrenia and neurodegenerative disorders, such as amyotrophic lateral sclerosis (Jaffrey and Wilkinson, 2018). TOB1, which codes for an antiproliferative protein that targets Frontiers in Genetics frontiersin.org mRNA deadenylation and decay (Hosoda et al, 2011), has previously been associated with neurodegenerative disorders (Weskamp and Barmada, 2018), such as multiple sclerosis (Gironi et al, 2016) and a TOB1 deletion has been associated with hippocampus-mediated acute stress response in animal models (Youssef et al, 2022). The primary role of the signal transduction pathway is to regulate overall growth and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In order to habituate awake mice to the MRI imaging protocol, an acclimation protocol was employed after the surgeries for head-fixation [16][17][18] . Male mice were fixed in a mock MRI environment and exposed to MRI imaging sounds and blue illumination for 2 h to habituate them to a leak of illumination during scanning (2.0 Hz).…”
Section: Acclimationmentioning
confidence: 99%
“…A previous optogenetic fMRI experiment activated DRN serotonin neurons using the Pet1 promoter under anesthesia and showed widespread suppression of cortical activities [15]. We introduced an acclimation protocol to allow stable fMRI recording in awake mice [1618] and found that DRN serotonin activation in an awake state induced increased brain-wide activity in both cortical and subcortical areas. In contrast, under anesthesia with isoflurane, DRN serotonin activation decreased activities in those areas, consistent with a previous study [15].…”
Section: Introductionmentioning
confidence: 99%